2021
DOI: 10.1159/000517478
|View full text |Cite
|
Sign up to set email alerts
|

Major Depressive Disorder Enhances Th2 and Th17 Cytokines in Patients Suffering from Allergic Rhinitis and Asthma

Abstract: <b><i>Introduction:</i></b> Major depressive disorder (MDD) can impact the severity of allergic rhinitis (AR) and asthma (AA). Here, we evaluated the cytokine production by T-cells from AR and AA patients with or without MDD. The effect of serotonin on the in vitro T-cell response was also evaluated. <b><i>Methods:</i></b> The cytokines produced by activated T-cells were measured by Luminex and flow cytometry. In some cell cultures, serotonin was added. <b>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 94 publications
1
14
0
3
Order By: Relevance
“…An association between IL-2, IL-6, IL-8, TNF-α and VEGF levels and the severity of depression have been reported [ 35 ]. Additionally, IL-5 and IL-17 production by T-cells from allergic asthma patients are reported to be positively associated with the severity of major depressive disorders [ 36 ]. In the current study, the amount of IL-1β, IL-2, IL-4, IL-5, IL-13 and IFN-γ in the serum of HDM-sensitized mice were significantly higher than PBS control mice, demonstrating that chronic nasal HDM administration leads to systemic increases in these pro-inflammatory and Th2-related cytokines that are potentially associated with depression.…”
Section: Discussionmentioning
confidence: 99%
“…An association between IL-2, IL-6, IL-8, TNF-α and VEGF levels and the severity of depression have been reported [ 35 ]. Additionally, IL-5 and IL-17 production by T-cells from allergic asthma patients are reported to be positively associated with the severity of major depressive disorders [ 36 ]. In the current study, the amount of IL-1β, IL-2, IL-4, IL-5, IL-13 and IFN-γ in the serum of HDM-sensitized mice were significantly higher than PBS control mice, demonstrating that chronic nasal HDM administration leads to systemic increases in these pro-inflammatory and Th2-related cytokines that are potentially associated with depression.…”
Section: Discussionmentioning
confidence: 99%
“…Major depressive disorder promotes the production of Th2- and Th17-related cytokines in patients with allergic rhinitis and asthma, which could be inhibited by 5-hydroxytryptamine treatment. Mechanistically, IL-5 and IL-17 levels are strongly correlated with the severity of depressive and anxiety symptoms [ 74 ].…”
Section: Cd4 + T Cells In Lung Homeostasismentioning
confidence: 99%
“…However, some animal studies on abnormal brain responses secondary to nasal immune-inflammatory responses after AR have been reported, and it has been suggested that brain regions such as hippocampus, cortex, and olfactory bulb are closely related to the development of mental disorders in AR animals ( 35 37 ). Along with the achievements in animal model studies, some authors have also conducted relevant experiments using blood samples and cells from depressed patients and AR patients, and confirmed the correlation between the neurotransmitter 5-hydroxytryptamine and the cytokines secreted by T lymphocytes during an allergic reaction ( 38 ).…”
Section: Causes and Mechanisms Of Depression In Armentioning
confidence: 89%